Artificial intelligence and digital marketing on online purchase intention mediating customer experience study on al washliyah university labuhanbatu students - Levianti, Rina Asriani (Institute of Computer Science (IOCS), 2024)
This research aims to analyze the influence of artificial intelligence and digital marketing on online purchase intention, with customer experience as a mediating factor among students at Al Washliyah University, Labuhanbatu, North Sumatra. This quantitative descriptive study targets a population comprising all students at Univa Labuhanbatu, from which a sample of 100 students was selected. Data were collected using a structured questionnaire designed on Google Forms and distributed via WhatsApp to ensure broad reach among participants. Structural Equation Modeling (SEM), facilitated by SmartPLS software, was employed to analyze the data. The findings of this study reveal several key insights: first, artificial intelligence has a positive and significant impact on purchase intention. Second, digital marketing similarly exerts a positive and significant effect on purchase intention. Third, customer experience is shown to effectively mediate the relationship between artificial intelligence and purchase intention, indicating that improved customer interactions enhance the AI’s impact on purchasing behaviors. Lastly, customer experience also mediates the relationship between digital marketing and purchase intention, demonstrating the importance of customer engagement in optimizing digital marketing effectiveness. These findings underscore the critical role of customer experience as a bridge linking AI and digital marketing efforts to purchasing intentions, especially within a university student demographic in a digital context